Factors associated with dental fluorosis - Rigo, Lilian (2010)
Purpose: To assess the prevalence and severity of dental fluorosis and its associated factors in teenagers attending schools with oral health programs. Methods: The sample consisted of 535 students (12- and 15-19-year-olds) living in a city in the Southern Region of Brazil. For data collection, clinical examinations were performed using the Dean’s index. Exploratory data on demographics, socioeconomic conditions, access to dental service and hygiene habits were collected using a semi-structured questionnaire. Data were analyzed by multiple logistic regression analysis. Results: The prevalence of dental fluorosis was 25% in this sample, and a very low level of fluorosis was the most frequent category found (18.3%). Fluorosis was associated with female gender (OR=1.55; CI95%1.03-2.32). Drinking water from an artesian well or bottled water was protective against fluorosis (OR=0.51; CI95% 0.27-0.95). Conclusion: The prevalence of dental fluorosis in this sample of students was high, but the fluorosis was of low severity. The type of drinking water and gender were shown to be determinant factors of fluorosis in the tested model.